Farmers’ Perception on Potato Pests and Yield Loss Assessment by Red Ant and White Grub on Potato in Ramechhap, Nepal - Khadka, Santosh; Koirala, Madhav; Tiwari, Susmita; Tiwari, Sundar (International Journal of Environment, 2021)
Survey was conducted to assess the knowledge and practices of potato growing farmers’ on the details of potato pests in Gokulganga Rural Municipality of the Ramechhap district. Fifty farmers’ were randomly selected and interviewed using structured open-ended questionnaire for collecting the information. Similarly, field yield loss by red ant and white grub on Cardinal and Rosita variety was assessed from one meter square area of thirty fields of the survey site. Survey revealed red ant followed by white grub were the major pest of potato. The average percentage yield loss by the red ant and white grub was 17.3% and 10.5%, respectively. It was also found that, Rosita variety was better in terms of yield than Cardinal. The percentage yield loss on Cardinal and Rosita variety was 15.59% and 6.11% by red ant and 2.01% and 4.16% by white grub, respectively. There is not significant difference in yield loss by red ant and white grub in between Cardinal and Rosita variety. The correlation between white grub population and percentage yield loss is moderately positive in both Cardinal (0.448) and Rosita (0.246) variety whereas correlation between red ant population and percentage yield loss is negative in Cardinal (-0.15) and less positive in Rosita (0.023) variety. Farmers’ knowledge and practices on potato pest management and field loss information can be useful to design integrated pest management strategy for potato pest management.